Subjective and objective financial toxicity among colorectal cancer patients: a systematic review - Azzani, Meram; Azhar, Zahir Izuan; Ruzlin, Aimi Nadira Mat; Wee, Chen Xin; Samsudin, Ely Zarina; Al-Harazi, Sabah Mohammed; Noman, Sarah (BioMed Central, 2024)
Background: Colorectal cancer (CRC) is the third most common cancer type worldwide. Colorectal cancer treatment costs vary between countries as it depends on policy factors such as treatment algorithms, availability of treatments and whether the treatment is government-funded. Hence, the objective of this systematic review is to determine the prevalence and measurements of financial toxicity (FT), including the cost of treatment, among colorectal cancer patients. Methods: Medline via PubMed platform, Science Direct, Scopus, and CINAHL databases were searched to find studies that examined CRC FT. There was no limit on the design or setting of the study. Results: Out of 819 papers identified through an online search, only 15 papers were included in this review. The majority (n = 12, 80%) were from high-income countries, and none from low-income countries. Few studies (n = 2) reported objective FT denoted by the prevalence of catastrophic health expenditure (CHE), 60% (9 out of 15) reported prevalence of subjective FT, which ranges from 7 to 80%, 40% (6 out of 15) included studies reported cost of CRC management– annual direct medical cost ranges from USD 2045 to 10,772 and indirect medical cost ranges from USD 551 to 795. Conclusions: There is a lack of consensus in defining and quantifying financial toxicity hindered the comparability of the results to yield the mean cost of managing CRC. Over and beyond that, information from some low-income countries is missing, limiting global representativeness.